Field notes contributed by Peter C. Petersen, summer 1993 - Petersen, Peter C.et al (1993)
Summer report of birds and locations contributed by Peter C. Petersen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1993. Plustek - flatbed